1990
DOI: 10.1128/jb.172.5.2675-2687.1990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular genetic characterization of the Bacillus subtilis gene (infB) encoding protein synthesis initiation factor 2

Abstract: Western blot (immunoblot) analysis of Bacillus subtilis cell extracts detected two proteins that cross-reacted with monospecific polyclonal antibody raised against Escherichia coli initiation factor 2a (IF2a). Subsequent Southern blot analysis of B. subtils genomic DNA identified a 1.3-kilobase (kb) Hindu fragment which cross-hybridized with both E. coli and Bacillus stearothermophilus IF2 gene probes. This DNA was cloned from a size-selected B. subtilis plasmid library. The cloned HindUI fragment, which was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
3
26
0
1
Order By: Relevance
“…3 encodes the last 40 amino acids of DNA polymerase III, the polC product. The presence of the polC gene in close proximity to infB is in good agreement with the previous determination of the infB chromosomal position (42 (Fig. 3).…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…3 encodes the last 40 amino acids of DNA polymerase III, the polC product. The presence of the polC gene in close proximity to infB is in good agreement with the previous determination of the infB chromosomal position (42 (Fig. 3).…”
Section: Methodssupporting
confidence: 92%
“…1-Galactosidase assays were performed on sonically disrupted extracts as described before (44) (42) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, T. thermophilus IF2 may not require a speci c region of its structure with high af nity for the ribosome. However, T. thermophilus IF2 may not have a strong interaction with the ribosome compared to E. coli IF2 since Vornlocher and coworkers (35) found that during the purication of T. thermophilus IF2, the factor was almost completely Overall a high sequence similarity is found towards the C-terminus of the protein opposite to the higher variability around the N-terminus (52)(53)(54)(55).…”
Section: Recognition Of the Ribosome By If2mentioning
confidence: 99%